The Role of Cover Crops in Sustainable Agriculture: Benefits, Challenges, and Future Directions - Khanal, Karishma (CV. Literasi Indonesia, 2025)
Cover crops provide several benefits, such as enhancing soil fertility, reducing weed pressure, improving water retention, and mitigating soil erosion. Several studies show they also play a vital role in carbon sequestration and mitigate climate change by reducing greenhouse gas emissions. In addition, the contribution to the long-term sustainability of regenerative agriculture systems is one significant role of cover crops. Though they offer multiple advantages, we face challenges like labor costs, managing complexity, and the need for tailored species selection based on environmental conditions. The paper helps to decipher the multiple benefits that cover crops offer, assesses the associated challenges, and discusses future directions for research and policy to build up their integration into modern agricultural practices. Also, studying the patterns of studies related to cover crops in the past decades helps us to understand previous outcomes and challenges. Documenting these challenges can be integral to regenerative agriculture systems that support long-term environmental sustainability and food security.